PENGEMBANGAN MODEL PEMBELAJARAN PENDIDIKAN JASMANI MOGI TIGA UNTUK PESERTA DIDIK TUNA DAKSA CEREBRAL PALSY - Alfogi, Dimas; Atesya Kesumawati, Selvi; Hardiyono, Bayu; Fikri, Aprizal (Fakultas Ilmu Keolahragaan Unimed, 2025)
This study aims to develop an adaptive game-based basic movement learning model for students with cerebral palsy (CP) in special elementary schools. The developed model, MOGI Three, was designed using the ADDIE approach (Analysis, Design, Development, Implementation, Evaluation). Validation by three experts indicated a high level of content validity (CVR = 0.15). Small-scale trials showed that most students achieved high to very high scores in basic motor skills. These findings indicate that MOGI Three is effective in improving active participation, postural control, and basic motor abilities in students with CP. The study concludes that MOGI Three is a feasible and applicable physical education model that supports inclusive education practices. Keywords: cerebral palsy, physical education, basic movement, game-based model, ADDIE